Discovering Islamic marketing potential in shaping blockchain-¬based halal logistic services: A bibliometric analysis - Fernando, Yudi; Hendayani, Ratih; Muhammed, Jawo; Syed Radzi, Rahamaddulla; Khairunnisa, Abdul Aziz; Nia, Maimunah (Emerald Publishing, 2024)
Purpose – This paper aims to examine the Islamic marketing literature to uncover potential customer adoption behaviours and enhance the effectiveness of blockchain-based halal logistics services in catering to customer demands. The findings of this paper provide substantial contributions to the realms of both halal logistics services and Islamic marketing literature, delineating future paths for research. By delving into halal logistics practices, integration procedures and service provider performance, this paper assists stakeholders in enhancing halal logistics services to meet the changing demands of customers effectively. Design/methodology/approach – This paper uses a systematic review incorporating bibliometric analysis to examine past and contemporary research topics, selecting and appraising contributions while analysing and consolidating data. A methodical approach has been used to identify, assess and incorporate pertinent studies on Islamic characteristics, traceability technology, blockchain integration and halal logistics practices. Findings – After screening and analysing 139 selected documents with the VOS viewer, it is evident that among a 1,000 keywords, 15 stand out in terms of frequency and link strength. The research highlights the considerable academic interest in themes such as “blockchain”, “halal logistics” and “supply chain”, underscoring their importance. The findings of this paper help bridge the gap in Islamic marketing by linking technology with religious values. It suggests that the integration of blockchain technology in halal logistics enhances operational efficiency while aligning with both operational and Islamic marketing principles, promoting ethical conduct and transparency as key enablers. Practical implications – The theoretical significance of this paper lies in establishing a correlation among three key research domains: technology, symbolised by blockchain; customer-centric operations, incorporating the halal supply chain and logistics within Islamic marketing. The outcomes reflect consumer behaviour and Shariah compliance. This integration has the potential to introduce innovative theoretical frameworks that encompass religious ethics in marketing, logistics and technological advancements. Originality/value – This paper comprehensively analyses the intersection between blockchain technology, halal logistics, supply chain management and Islamic marketing. The paper has comprehensively analysed previous studies and outlined the future research path for blockchain technology in halal logistics and its application in Islamic marketing literature.